Mechanical behavior of CFRP partially confined coal cylinders under uniaxial compression - Qingwen Li; Ling Li; Chuangchuang Pan; Yuqi Zhong; Fanfan Nie; Hao Yang (PLoS ONE, 2025)
The loss of bearing capacity in abandoned coal pillars within air-mining areas is prone to cause surface settlement issues, which poses a serious threat to the safety of surface buildings. This paper thoroughly investigates the mechanical behavior of carbon fiber reinforced plastic (CFRP) partially-confined coal cylinders under uniaxial compression, aiming to explore a cost-effective technology for reinforcing coal pillars. The influence of CFRP strips on the axial compression performance of coal cylinders was systematically analyzed by adjusting two parameters: the net spacing ratio and the number of CFRP strip layers. The study shows that CFRP strip partially-confined coal cylinders and fully-confined coal cylinders exhibit similar mechanical properties, and the failure of partially-confined coal cylinders is mainly characterized by the fracture of CFRP strips and the localized fracturing of the coal cylinder. As the net spacing ratio decreases and the number of CFRP layers increases, the peak strength and deformation capacity of the coal cylinders are significantly improved, with the maximum enhancement rate reaching up to 409.36%. Under different confining conditions, the energy evolution pattern of CFRP-confined coal cylinders is generally consistent, with energy primarily accumulating in the form of elastic energy prior to reaching peak strength, and dissipated energy increasing sharply after peak strength is reached. Considering factors such as equivalent thickness, the amount of CFRP material used, and a comprehensive evaluation of economic benefits and performance enhancement, the optimal solution was identified as the CFRP confinement with a net spacing ratio of 0.25 and six layers of wrapping, offering the most cost-effective option.